Historical evolution of verb conjugation transitions in modern Eastern Armenian - Khachatryan, Alvard (Bulletin of Yerevan University B: Philology, 2022)
The diachronic study of shifts in verbal conjugations is important from the point of view of identifying following changes in the general verbal system of the language. Thematic vowel transitions lead to changes in verb conjugations, along with which the forms and amount of verb conjugations change, so the types of transitional thematic vowels are also limited. This article discusses Modern Eastern Armenian verbs in comparison with their Old Armenian and Middle Armenian prototypes, and highlights the most common forms of thematic vowel transitions in terms of expression and content. In Old Armenian and Middle Armenian, verb transitions մ-իմ are common, and in modern Eastern Armenian - ամ-եմ and եմ-անամ, in which verbs of a neutral voice predominate. In modern Eastern Armenian, the thematic vowels of Grabar and Middle Armenian ի and ու are no longer applicable, and the verbs of these two conjugations have mainly switched to the thematic vowel ե, they, in turn, are modified in many dialects of the Eastern Armenian language, becoming ի: բերել-պիրիլ, սիրել-սիրիլ, գրել-գրիլ (Tavush region). In literary and colloquial versions, some ancient Armenian conjugation verbs ե and ի go into the verbs of conjugation: ճչել-ճչալ, երեւիլ-երեւալ, խօսել(իմ)-խոսալ, ծիծաղել(իմ)-ծիծաղալ and others.